Calendar of Events. (Communications of the ACM, 2012)
The article presents a calendar of events relating to computer science including the Eighth Asia Information Retrieval Societies Conference in Tianjin, China from December 17-18, 2012, the International Conference on Distributed Computing and Networking in Mumbai, India from January 3-6, 2013, and Innovations in Theoretical Computer Science in Berkeley, California from January 9-12, 2013.